A kind of activated carbon that can be recycled and its preparation method

By mixing with materials such as manganic acid, high -performance activated carbon is prepared, and the adhesive prepared by sodium silicate and polyvinyl alcohol is improved, which solves its strength. The problem realizes efficient desulfurization and denitration and renewable use.

CN118949926BActive Publication Date: 2025-01-28广东韩研活性炭科技股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411029263.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-01-28
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The existing activated carbons lack performance and strength during the desulfurization and denitrification process, resulting in poor adsorption and removal effects.

Method used

By mixing with materials such as fruit shells with manganic acid, after carbonization, activation, and modification treatment, the activated carbon with high ratio and excellent adsorption performance is prepared, and the lumic carbon is improved through the adhesive prepared by sodium silicate and polyvinyl alcohol. strength.

Benefits of technology

It has significantly improved the performance and mechanical strength of littering carbon, enhanced its adsorption activity, and realized renewable use, which is in line with the concept of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004969466150000081
    Figure BDA0004969466150000081
  • Figure BDA0004969466150000091
    Figure BDA0004969466150000091
Patent Text Reader

Abstract

The present invention relates to a renewable activated carbon and a preparation method thereof, belonging to the technical field of activated carbon. The preparation method comprises the following steps: S1, pretreatment; S2, preparation of modified carbon; S3, preparation of activated carbon finished product. The present invention uses fruit shell material as raw material to prepare activated carbon, uses zinc chloride as an activator, and uses manganese ferrite to increase the specific surface area of ​​activated carbon; adds ferric chloride hexahydrate and nickel nitrate hexahydrate to enhance the adsorption activity of activated carbon, and also mixes calcium oxide to introduce carbonate groups, thereby expanding the contact area between activated carbon and pollutants and improving the desulfurization and denitrification performance of activated carbon. In addition, the present invention also makes a self-made adhesive, adds sorbitol and sodium carboxymethyl cellulose in the preparation of the adhesive to enhance the viscosity and stability of the adhesive, and uses the adhesive to prepare activated carbon so that the prepared activated carbon has excellent strength. The finished activated carbon prepared by the present invention also has good renewable performance and can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon, and in particular relates to a recyclable activated carbon and a preparation method thereof. Background Art

[0002] With the acceleration of the global industrialization process and the continuous improvement of urbanization, the problem of air pollution is becoming increasingly serious. Sulfur oxides (SOx) and nitrogen oxides (NOx), as the main air pollutants, not only pose a serious threat to human health, but also cause environmental problems such as acid rain and photochemical smog, which have a huge impact on the ecosystem and economic and social development. Therefore, the research and development of efficient desulfurization and denitrification technologies has become an important topic in the field of environmental protection. Activated carbon, as an adsorption material with excellent adsorption capacity and broad application prospects, shows great potential in the field of desulfurization and denitrification. However, the desulfurization and denitrification performance and mechanical strength of the activated carbon currently on the market are relatively poor, resulting in the problems of loose activated carbon, poor adsorption and removal effect during use. Therefore, it is very important to develop an activated carbon with excellent desulfurization and denitrification performance and high strength. Summary of the invention

[0003] The purpose of the present invention is to provide a renewable activated carbon and a preparation method thereof, which solves the problem of poor desulfurization and denitrification performance and strength in the existing activated carbon technology.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A method for preparing renewable activated carbon, the method comprising the following steps:

[0006] S1. Pretreatment: removing impurities from the fruit shell, washing, drying under temperature control, and crushing the fruit shell, uniformly mixing the crushed fruit shell and manganese ferrite, carbonizing, and cooling to obtain intermediate carbon A;

[0007] S2, preparing modified carbon: mixing intermediate carbon A and zinc chloride solution and stirring, filtering, taking filter residue and temperature-controlled activation, cooling, adding ferric chloride hexahydrate solution and nickel nitrate hexahydrate solution and magnetic stirring, filtering, taking filter residue and temperature-controlled drying, and after drying, adding calcium oxide and blending and stirring to obtain intermediate carbon B;

[0008] S3. Preparation of finished activated carbon products: the binder, vanadium pentoxide and intermediate carbon B are mixed evenly, dried under controlled temperature, pressed into shape, carbonized under controlled temperature, and finally activated under controlled temperature and pressure to obtain finished activated carbon products.

[0009] As a preferred technical solution of the present invention, the fruit shell in step S1 includes at least one of coconut shell, walnut shell, apricot shell and almond shell.

[0010] Furthermore, the mass ratio of the coconut shell, walnut shell, apricot shell and almond shell is 1.1-1.4:1-1.2:0.8-1:0.6-0.8.

[0011] As a preferred technical solution of the present invention, the mass ratio of the crushed fruit shell to manganese ferrite in step S1 is 1:0.1-0.12.

[0012] Furthermore, the particle size of the manganese ferrite is 50 nm.

[0013] As a preferred technical solution of the present invention, the washing in step S1 is washing with deionized water for 2-3 times; the temperature-controlled drying is drying at 40-50°C to constant weight; the crushing is crushing to 2-3 mm; the carbonization is carbonizing at 400-450°C for 3-4 hours under a nitrogen atmosphere; and the cooling is cooling to room temperature.

[0014] Furthermore, the flow rate of the nitrogen atmosphere is 120-150 mL / min.

[0015] As a preferred technical solution of the present invention, the mass ratio of the intermediate carbon A, zinc chloride solution, ferric chloride hexahydrate solution, nickel nitrate hexahydrate solution and calcium oxide in step S2 is 1:1.4-1.6:0.10-0.14:0.12-0.15:0.08-0.1.

[0016] Furthermore, the calcium oxide has a mesh size of 180-200.

[0017] As a preferred technical solution of the present invention, the mass fraction of the zinc chloride solution in step S2 is 40-50%; the concentration of the ferric chloride hexahydrate solution is 0.4-0.5 mol / L; and the concentration of the nickel nitrate hexahydrate solution is 0.1-0.15 mol / L.

[0018] As a preferred technical solution of the present invention, the mixing and stirring time in step S2 is 30-40 minutes; the temperature-controlled activation is to activate at a temperature of 500-550°C for 1-2 hours under a carbon dioxide atmosphere; the cooling is to cool to room temperature; the magnetic stirring time is 10-12 hours; the temperature of the temperature-controlled drying is 70-80°C; and the blending and stirring time is 1-2 hours.

[0019] Furthermore, the flow rate of the carbon dioxide atmosphere is 150-170 mL / min.

[0020] As a preferred technical solution of the present invention, the mass ratio of the binder, vanadium pentoxide and intermediate carbon B in step S3 is 2.5-3:1.3-1.5:5.5-6.

[0021] Furthermore, the preparation method of the binder is: sodium silicate, polyvinyl alcohol solution and hydrochloric acid solution are mixed evenly, stirred under temperature control, and then sorbitol and sodium carboxymethyl cellulose are added in sequence and stirred to obtain the binder.

[0022] Furthermore, the mass ratio of the sodium silicate, the polyvinyl alcohol solution, the hydrochloric acid solution, the sorbitol and the sodium carboxymethyl cellulose is 0.3-0.35:9.5-10:2-2.5:0.0006-0.0007:0.0009-0.001.

[0023] Furthermore, the mass fraction of the polyvinyl alcohol solution is 8-10wt%; and the concentration of the hydrochloric acid solution is 1 mol / L.

[0024] Furthermore, the temperature of the temperature-controlled stirring is 65-75° C., and the time is 1.5-2 hours; and the stirring time of adding sorbitol and sodium carboxymethyl cellulose in sequence is 1-2 hours.

[0025] As a preferred technical solution of the present invention, the temperature of the temperature-controlled drying in step S3 is 55-60°C; the temperature of the temperature-controlled carbonization is 550-600°C, and the time is 1.5-2h; the temperature of the temperature-controlled and pressure-controlled activation is 700-740°C, the pressure is 80-90Pa, and the time is 1-1.5h.

[0026] As a preferred technical solution of the present invention, the present invention also provides an activated carbon prepared by the above preparation method.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention uses fruit shell material as a raw material to prepare activated carbon, uses zinc chloride as an activator, and uses manganese ferrite to promote the burning loss of carbon atoms, thereby cooperating with zinc chloride to promote the development of activated carbon pores, thereby increasing the specific surface area of ​​the activated carbon; on this basis, ferric chloride hexahydrate is added to introduce the iron element, and nickel nitrate hexahydrate is used to introduce the nickel element. Iron and nickel coexist in the system, which enhances the interaction with the activated carbon, allowing iron and nickel particles to exist in the activated carbon in a small size state, thereby enhancing the adsorption activity of the activated carbon. At the same time, the present invention also mixes calcium oxide, introduces carbonate groups into the system with calcium oxide, increases the content of oxygen-containing functional groups on the surface of the activated carbon, expands the contact area between the activated carbon and the pollutants to a certain extent, and improves the desulfurization and denitrification performance of the activated carbon.

[0029] (2) The present invention uses sodium silicate and polyvinyl alcohol to prepare a binder for activated carbon. A network structure is formed in the system. On this basis, sorbitol with a certain water absorption is added to the surface of the sodium silicate, which effectively increases the hardening speed of the binder and makes the network structure more stable and firm. Sodium carboxymethyl cellulose is added to effectively assist sorbitol in improving the stability and uniformity of the binder with its advantages of adhesion and structural stability. Therefore, the use of the binder in the preparation of activated carbon can effectively make the prepared activated carbon have excellent strength.

[0030] (3) The activated carbon product prepared by the present invention has good renewability and can be recycled, which is in line with the concept of sustainable development, saves resources and energy, and effectively saves long-term use costs. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The manganese ferrite used in the embodiment of the present invention is nano-grade and purchased from Hubei Maidehao Chemical Co., Ltd., model MDH; it will not be described in detail later.

[0033] Example 1

[0034] A method for preparing renewable activated carbon, the method comprising the following steps:

[0035] S1. Pretreatment: remove impurities from coconut shell, wash with deionized water for 3 times, dry at 40°C to constant weight, crush to 2 mm, mix the crushed shell and 50 nm manganese ferrite evenly, carbonize at 425°C for 3 h in nitrogen atmosphere, and cool to obtain intermediate carbon A;

[0036] The mass ratio of the crushed fruit shell to manganese ferrite is 1:0.11; the flow rate of the nitrogen atmosphere is 120 mL / min;

[0037] S2, preparation of modified carbon: intermediate carbon A and 40% by mass zinc chloride solution were mixed and stirred for 40 minutes, filtered, the filter residue was activated at 500°C in a carbon dioxide atmosphere for 1 hour, cooled, 0.45 mol / L ferric chloride hexahydrate solution and 0.13 mol / L nickel nitrate hexahydrate solution were added and magnetically stirred for 10 hours, filtered, the filter residue was dried at 70°C for 2 hours, and after drying, 50 nm manganese ferrite and 190 mesh calcium oxide were added and blended and stirred to obtain intermediate carbon B;

[0038] The flow rate of the carbon dioxide atmosphere is 170 mL / min;

[0039] The mass ratio of the intermediate carbon A, zinc chloride solution, ferric chloride hexahydrate solution, nickel nitrate hexahydrate solution and calcium oxide is 1:1.4:0.1:0.12:0.09;

[0040] S3, preparation of activated carbon finished product: the binder, vanadium pentoxide and intermediate carbon B are mixed evenly in a mass ratio of 2.5:1.3:6, and then dried at 55°C, pressed into shape, and then carbonized at 550°C for 1.5h, and finally activated at 700°C and 90Pa for 1h to obtain the activated carbon finished product;

[0041] The preparation method of the binder is as follows: sodium silicate, a polyvinyl alcohol solution with a mass fraction of 9wt% and a hydrochloric acid solution with a concentration of 1mol / L are mixed evenly, the temperature is controlled at 65°C and stirred for 2h, and then sorbitol and sodium carboxymethyl cellulose are added in sequence and stirred for 1h to obtain the binder;

[0042] The mass ratio of the sodium silicate, the polyvinyl alcohol solution, the hydrochloric acid solution, sorbitol and sodium carboxymethyl cellulose is 0.35:9.5:2:0.0006:0.0009.

[0043] Example 2

[0044] A method for preparing renewable activated carbon, the method comprising the following steps:

[0045] S1. Pretreatment: remove impurities from walnut shells and apricot shells at a mass ratio of 1.1:0.9, wash twice with deionized water, dry to constant weight at 45°C, crush to 3 mm, mix the crushed shells and 50 nm manganese ferrite evenly, carbonize at 400°C for 3 h in a nitrogen atmosphere, and cool to obtain intermediate carbon A;

[0046] The mass ratio of the crushed fruit shell to manganese ferrite is 1:0.1; the flow rate of the nitrogen atmosphere is 135 mL / min;

[0047] S2, preparation of modified carbon: intermediate carbon A and 45% zinc chloride solution were mixed and stirred for 30 min, filtered, the filter residue was activated at 550°C in a carbon dioxide atmosphere for 1.5 h, cooled, 0.5 mol / L ferric chloride hexahydrate solution and 0.15 mol / L nickel nitrate hexahydrate solution were added and magnetically stirred for 11 h, filtered, the filter residue was dried at 75°C for 1 h, 50 nm manganese ferrite and 200 mesh calcium oxide were added and mixed and stirred to obtain intermediate carbon B;

[0048] The flow rate of the carbon dioxide atmosphere is 150 mL / min;

[0049] The mass ratio of the intermediate carbon A, zinc chloride solution, ferric chloride hexahydrate solution, nickel nitrate hexahydrate solution and calcium oxide is 1:1.6:0.13:0.15:0.08;

[0050] S3, preparation of activated carbon finished product: the binder, vanadium pentoxide and intermediate carbon B are mixed evenly in a mass ratio of 3:1.4:5.5, and then dried at 58°C, pressed into shape, and then carbonized at 600°C for 2h, and finally activated at 720°C and 80Pa for 1h to obtain the activated carbon finished product;

[0051] The preparation method of the binder is as follows: sodium silicate, a polyvinyl alcohol solution with a mass fraction of 8wt% and a hydrochloric acid solution with a concentration of 1mol / L are mixed evenly, the temperature is controlled at 70°C and stirred for 1.5h, and then sorbitol and sodium carboxymethyl cellulose are added in sequence and stirred for 1.5h to obtain the binder;

[0052] The mass ratio of the sodium silicate, the polyvinyl alcohol solution, the hydrochloric acid solution, sorbitol and sodium carboxymethyl cellulose is 0.3:10:2.3:0.0006:0.001.

[0053] Example 3

[0054] A method for preparing renewable activated carbon, the method comprising the following steps:

[0055] S1. Pretreatment: remove impurities from the almond shell, wash it with deionized water twice, dry it at 50°C to constant weight, crush it to 3 mm, mix the crushed shell and 50 nm manganese ferrite evenly, carbonize it at 450°C for 4 h in a nitrogen atmosphere, and cool it to obtain intermediate carbon A;

[0056] The mass ratio of the crushed fruit shell to manganese ferrite is 1:0.12; the flow rate of the nitrogen atmosphere is 150 mL / min;

[0057] S2, preparation of modified carbon: intermediate carbon A and 50% by mass zinc chloride solution were mixed and stirred for 35 minutes, filtered, the filter residue was activated at 525°C in a carbon dioxide atmosphere for 2 hours, cooled, 0.4 mol / L ferric chloride hexahydrate solution and 0.1 mol / L nickel nitrate hexahydrate solution were added and magnetically stirred for 12 hours, filtered, the filter residue was dried at 80°C for 1.5 hours, and after drying, 50 nm manganese ferrite and 180 mesh calcium oxide were added and blended and stirred to obtain intermediate carbon B;

[0058] The flow rate of the carbon dioxide atmosphere is 160 mL / min;

[0059] The mass ratio of the intermediate carbon A, zinc chloride solution, ferric chloride hexahydrate solution, nickel nitrate hexahydrate solution and calcium oxide is 1:1.5:0.14:0.14:0.1;

[0060] S3, preparation of activated carbon product: the binder, vanadium pentoxide and intermediate carbon B are mixed evenly in a mass ratio of 2.7:1.5:5.8, dried at 60°C, pressed into shape, carbonized at 575°C for 2h, and finally activated at 740°C and 85Pa for 1.5h to obtain the activated carbon product;

[0061] The preparation method of the binder is as follows: sodium silicate, a polyvinyl alcohol solution with a mass fraction of 10wt% and a hydrochloric acid solution with a concentration of 1mol / L are mixed evenly, the temperature is controlled at 75°C and stirred for 2h, and then sorbitol and sodium carboxymethyl cellulose are added in sequence and stirred for 2h to obtain the binder;

[0062] The mass ratio of the sodium silicate, the polyvinyl alcohol solution, the hydrochloric acid solution, sorbitol and sodium carboxymethyl cellulose is 0.32:9.7:2.5:0.0007:0.001.

[0063] Comparative Example 1

[0064] Compared with Example 1, the difference is that manganese ferrite is not added in step S1 of Comparative Example 1, and the remaining operating steps and parameters are the same.

[0065] Comparative Example 2

[0066] Compared with Example 1, the difference is that in step S2 of Comparative Example 2, no ferric chloride hexahydrate solution is added, that is, the mass ratio of intermediate carbon A, zinc chloride solution, nickel nitrate hexahydrate solution and calcium oxide is 1:1.4:0.22:0.09; the remaining operating steps and parameters are the same.

[0067] Comparative Example 3

[0068] Compared with Example 1, the difference is that in step S2 of Comparative Example 3, nickel nitrate hexahydrate solution is not added, that is, the mass ratio of intermediate carbon A, zinc chloride solution, ferric chloride hexahydrate solution and calcium oxide is 1:1.4:0.22:0.09; the remaining operating steps and parameters are the same.

[0069] Comparative Example 4

[0070] Compared with Example 1, the difference is that calcium oxide is not added in step S2 of Comparative Example 4, and the remaining operating steps and parameters are the same.

[0071] Comparative Example 5

[0072] Compared with Example 1, the difference is that in step S3 of Comparative Example 5, sorbitol is not added, that is, the mass ratio of sodium silicate, polyvinyl alcohol solution, hydrochloric acid solution and sodium carboxymethyl cellulose is 0.35:9.5:2:0.0015, and the remaining operating steps and parameters are the same.

[0073] Comparative Example 6

[0074] Compared with Example 1, the difference is that in step S3 of Comparative Example 6, sodium carboxymethyl cellulose is not added, that is, the mass ratio of sodium silicate, polyvinyl alcohol solution, hydrochloric acid solution and sorbitol is 0.35:9.5:2:0.0015, and the remaining operating steps and parameters are the same.

[0075] Test Example 1

[0076] The simulated flue gas components are SO21000ppm, NO500ppm, NH3500ppm, O25%, H2O5%, and N2 as the balance gas. The adsorption temperature is 150℃, the total flue gas flow rate is 300mL / min, and the space velocity of the adsorption process is 5700 / h.

[0077] This test is carried out in a fixed bed flow reactor, and 10g of the finished activated carbon products obtained in Examples 1-3 and Comparative Examples 1-4 are respectively placed in the quartz glass tube of the fixed bed reactor, and the temperature difference of the reactor is controlled within 1°C. The fixed bed reactor is heated to 200°C and stabilized. First, high-purity nitrogen is blown in so that the SO2, CO, NO and CO2 measured by the flue gas analyzer are close to zero, and then the gas distribution gas path is switched to pass simulated flue gas. The reaction product is measured by the flue gas analyzer. The simulated flue gas is passed for 1 hour. The conversion rate is calculated based on the product. Alkaline lime water is used as the tail gas absorption liquid, and the desulfurization and denitrification efficiency of each activated carbon product is calculated respectively. The activated carbon regeneration method involved in the present invention is a conventional water washing regeneration method in the art, that is, the finished activated carbon is placed in deionized water for ultrasonic vibration for 10 minutes, and the regeneration is completed after drying, and it is placed in a quartz glass tube for recycling; the desulfurization and denitrification results after desulfurization and denitrification and regeneration once are shown in Table 1.

[0078] Table 1

[0079]

[0080]

[0081] It can be seen from Table 1 that the activated carbon product prepared by the present invention has excellent desulfurization and denitrification effects and can be recycled.

[0082] Test Example 2

[0083] According to GB / T12496.6-1999, the activated carbon strength test was performed on the activated carbon products obtained in Examples 1-3 and Comparative Examples 5-6. The results are shown in Table 2.

[0084] Table 2

[0085] Activated carbon strength (%) Example 1 96 Example 2 95 Example 3 95 Comparative Example 5 84 Comparative Example 6 80

[0086] As can be seen from Table 2, the finished activated carbon product prepared by the present invention has excellent strength. This is because the present invention uses sodium silicate and polyvinyl alcohol to prepare the activated carbon binder, a network structure is formed in the system, and on this basis, sorbitol with a certain water absorption is added to the surface of sodium silicate, which effectively improves the hardening speed of the binder and makes the network structure more stable and firm. Sodium carboxymethyl cellulose is added, which effectively assists sorbitol in improving the stability and uniformity of the binder with its advantages of adhesion and structural stability. Therefore, the use of the binder in preparing activated carbon can effectively make the prepared activated carbon have excellent strength.

[0087] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0088] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing renewable activated carbon, characterized in that: The preparation method specifically comprises the following steps: S1. Pretreatment: removing impurities from the fruit shell, washing it, drying it under controlled temperature, crushing it, mixing the crushed fruit shell and manganese ferrite evenly, carbonizing it, and cooling it to obtain intermediate carbon A; The mass ratio of the crushed husk to manganese ferrite is 1:0.1-0.12; S2, preparing modified carbon: mixing intermediate carbon A and zinc chloride solution and stirring, filtering, taking filter residue and temperature-controlled activation, cooling, adding ferric chloride hexahydrate solution and nickel nitrate hexahydrate solution and magnetic stirring, filtering, taking filter residue and temperature-controlled drying, and after drying, adding calcium oxide and blending and stirring to obtain intermediate carbon B; The mass ratio of the intermediate carbon A, zinc chloride solution, ferric chloride hexahydrate solution, nickel nitrate hexahydrate solution and calcium oxide is 1:1.4-1.6:0.10-0.14:0.12-0.15:0.08-0.1; The temperature-controlled activation is to activate at 500-550° C. for 1-2 hours under a carbon dioxide atmosphere; S3, preparing the finished activated carbon product: the binder, vanadium pentoxide and intermediate carbon B are mixed evenly, dried under controlled temperature, pressed into shape, carbonized under controlled temperature, and finally activated under controlled temperature and pressure to obtain the finished activated carbon product; The mass ratio of the binder, vanadium pentoxide and intermediate carbon B is 2.5-3:1.3-1.5:5.5-6; The temperature of the temperature-controlled carbonization is 550-600°C, and the time is 1.5-2h; the temperature of the temperature-controlled and pressure-controlled activation is 700-740°C, the pressure is 80-90Pa, and the time is 1-1.5h; The preparation method of the binder is as follows: sodium silicate, polyvinyl alcohol solution and hydrochloric acid solution are mixed evenly, stirred under controlled temperature, and then sorbitol and sodium carboxymethyl cellulose are added in sequence and stirred to obtain the binder; the mass ratio of the sodium silicate, polyvinyl alcohol solution, hydrochloric acid solution, sorbitol and sodium carboxymethyl cellulose is 0.3-0.35:9.5-10:2-2.5:0.0006-0.0007:0.0009-0.

001.

2. The method for preparing renewable activated carbon according to claim 1, characterized in that: In step S1, the washing is performed with deionized water for 2-3 times; the temperature-controlled drying is performed at 40-50°C to constant weight; the crushing is performed to 2-3 mm; the carbonization is performed at 400-450°C for 3-4 hours under a nitrogen atmosphere; and the cooling is performed to room temperature.

3. The method for preparing renewable activated carbon according to claim 1, characterized in that: The mixing and stirring time in step S2 is 30-40 minutes; the cooling is cooling to room temperature; the magnetic stirring time is 10-12 hours; the temperature of the temperature-controlled drying is 70-80°C; and the blending and stirring time is 1-2 hours.

4. The method for preparing renewable activated carbon according to claim 1, characterized in that: In the preparation method of the binder, the temperature of temperature control stirring is 65-75°C and the time is 1.5-2h; and the stirring time of adding sorbitol and sodium carboxymethyl cellulose in sequence is 1-2h.

5. The method for preparing renewable activated carbon according to claim 1, characterized in that: The temperature of the temperature-controlled drying in step S3 is 55-60°C.

6. An activated carbon prepared by the method for preparing renewable activated carbon as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method and application of sludge carbonization and modification magnetic nanometer material capable of activating persulfate to realize printing and dyeing wastewater treatment

    CN106669727A

  • Modified activated carbon for desulfurization and denitrification and preparation process thereof

    CN115672306A